Why are microcredit interest rates in sub-Saharan Africa so persistently high? Testing the predictions of theoretical models - Chikalipah, Sydney (Department of Finance and Tax, 2022)
The microfinance industry is progressing towards becoming a core of financial inclusion in the sub-Saharan African (SSA) region. Despite the recent growth of microfinance in the SSA, that industry is seemingly characterised by high lending rates. Those high rates have become a hotly debated topic amongst microfinance stakeholders. It is against this background that this study first investigates the factors that influence the persistently high microcredit interest rates in SSA; it does so by utilising a panel dataset assembled from the Microfinance Information eXchange (MIX) market, the Heritage Foundation, and the World Bank, covering the period 2003 to 2011. Secondly, this study examines the determinants of financial inclusion in SSA, using a cross-sectional dataset obtained from Statista and the Global Findex for the year 2014. Several empirical approaches are used in the study: Bayesian Model Averaging, fixed effects, Generalised Method of Moments, and Ordinary Least Squares. The results reveal evidence of the following: (i) the operating costs associated with providing small loans, unexploited economies of scale, and institutional deficiencies all contribute towards increasing the microcredit interest rates; and (ii) volatile macroeconomic fundamentals exert undesirable effects on the microcredit interest rates. Second, a methodical analysis of the relationship between outreach to the poor and the financial performance of microfinance institutions (MFIs), produced the following findings: (i) providing smaller microcredits is associated with lower operating profit, and the exact opposite is true; and (ii) outreach to the poor clients is significantly related to a stronger financial performance. Third, the results of the determinants of financial inclusion demonstrate that illiteracy negatively affects financial inclusion in SSA. Overall, the study's empirical findings suggest that the following approach is needed to promote low microcredit interest rates. First, MFIs must be supported to expand outreach, and adopt digital technology to drive operational efficiency; second, countries in SSA must strengthen the prevailing weak institutional environment in the region; and third, macroeconomic policy regimes must be moderated, particularly by maintaining low and stable inflation rates. In relation to financial inclusion, countries in SSA must be committed to fighting functional illiteracy. All this could contribute to a financial inclusion agenda and towards poverty eradication in the SSA region.